GALLIC ACID: A PHENOLIC ACID AND ITS ANTIOXIDANT ACTIVITY FROM STEM BARK OF CHLOROFORM EXTRACTS OF SYZYGIUM LITORALE (BLUME) AMSHOFF (MYRTACEAE) - Tukiran Tukiran; Fitriyatul Mahmudah; Nurul Hidayati; Kuniyoshi Shimizu (Universitas Jenderal Soedirman, 2016)
A phenolic acid had been isolated from chloroform soluble fractions of a methanol extract of stem bark of Syzygium litorale, Fam. Myrtaceae. The structure of the isolated compound was elucidated and established as gallic acid through extensive spectroscopic studies (UV-Vis, FTIR, and NMR) and by comparison with literature data and authentic sample. This is the first report of the isolation of compound from this plant, although it has previously been found in Myrtaceae family such as S. aromaticum, S. cumini, S. polyanthum, S. cordatum, etc. The chloroform fraction, isolated compound, and vitamin C showed very strong antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) with IC50 value of 23.2, 7.5, and 12.5 mg/mL, respectively.